Depth dependant element analysis of PbMg1/3Nb2/3O3 using muonic x-rays. (28th February 2018) - Brown, K L; Stockdale, C P J; Luo, H; Zhao, X; Li, J-F; Viehland, D; Xu, G; Gehring, P M; Ishida, K; Hillier, A D; Stock, C
Abstract: The relaxor PbMg1/3 Nb2/3 O3 (PMN) has received attention due to its potential applications as a piezoelectric when doped with PbTiO3 (PT). Previous results have found that there are two phases existing in the system, one linked to the near-surface regions of the sample, the other in the bulk. However, the exact origin of these two phases is unclear. In this paper, depth dependant analysis results from negative muon implantation experiments are presented. It is shown that the Pb content is constant throughout all depths probed in the sample, but the Mg and Nb content changes in the near-surface region below 100 μ m. At an implantation depth of 60 μ m, it is found that there is a 25% increase in Mg content, with a simultaneous 5% decrease in Nb content in order to maintain charge neutrality. These results show that the previously observed skin effects in PMN are due to a change in concentration and unit cell.